Participatory environmental governance of infrastructure projects affecting reindeer husbandry in the Arctic - Landauer, Mia; Komendantova, Nadejda (Journal of environmental management, 2018)
Several infrastructure projects are under development or already operational across the Arctic region. Often the deployment of such projects creates benefits at the national, regional, or global scales. However, local communities can experience negative impacts due to the requirements for extensive land areas, which cause pressure on traditional land use. Public participation in environmental planning such as Environmental Impact Assessment (EIA) enables local communities to provide feedback on the environmental, social, and economic challenges of infrastructure projects. Ideally, participation can improve the means of social learning for all involved parties and help to co-develop sustainable solutions. The subject of our research is reindeer herders' participation in EIA procedures of mines and wind farms in Finland because these types of projects affect reindeer husbandry. We study empirically how stakeholders involved in the EIAs perceive the participation of reindeer herders in the planning and implementation of infrastructure projects, and how these differ from the perceptions of the reindeer herders who are affected by the infrastructure projects. Our qualitative data is based on in-depth semi-structured interviews (N = 31) with members of the industry sector, consultants, governmental authorities, and representatives of local communities; in this study, the reindeer herders. The results show that herders' level of participation in the EIAs and the benefits and challenges of participation are perceived differently. Furthermore, the regulatory framework does not adequately ensure that the developer carries social and environmental responsibilities throughout the infrastructure project's lifetime, and that regular communication with herders will also be maintained after the EIAs. Herders' expertise should be used throughout the project lifetime. For example, more attention should be paid to both negotiating possible options for compensation and monitoring mechanisms when the infrastructure projects are pre-screened for the EIAs, as well as to co-designing the different project alternatives with herders for the EIAs. •Perceptions on the herders' participation in the EIA vary between stakeholder types.•Sustained two-ways communication is important during the entire project lifetime.•Broader understanding of cumulative impacts in the EIAs is essential.•Regulatory steering needed to address monitoring and compensation responsibilities.